PENGARUH KEPEMILIKAN MANAJERIAL INSTITUSIONAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2021 - Simbolon, Lenni PL; Munthe, Kornel; Purba, Antonius M; Parhusip, Poltak Theodorus; Purba, Imelda Rimenda (UNIKA Santo Thomas, 2023)
This study aims to analyze and determine the effect of managerial ownership, institutional ownership and profitability on company value in manufacturing companies listed on the IDX for the 2018-2021 period. The type of data used in this study is secondary data with documentation techniques obtained from financial reports published on the IDX. The population in this study were 195 companies, using a purposive sampling method to obtain a sample of 22 companies. The data analysis technique used is multiple linear regression but first the classical assumption test is carried out and the hypothesis testing is done using the t test. The results of the study show that partially managerial ownership has a negative and insignificant effect on company value, institutional ownership and profitability have a positive, significant effect on company value in manufacturing companies listed on the IDX for the 2018-2021 period.